Graphene-based Q-switched pulsed fiber laser in a linear configuration - Yap, Yuen Kiat; De La Rue, Richard Michael; Pua, Chang Hong; Harun, Sulaiman Wadi; Ahmad, Harith (Optical Society of America, 2012)
A pulsed laser system is realized with graphene employed as a Q-switch. The graphene is exfoliated from its solution using an optical deposition and the optical tweezer effect. A fiber ferrule that already has the graphene deposited on it is inserted into an erbium-ytterbium laser (EYL) system with linear cavity configuration. We successfully demonstrate a pulsed EYL with a pulse duration of approximately 5.9 μs and a repetition rate of 20.0 kHz.